2020
DOI: 10.1002/rth2.12428
|View full text |Cite
|
Sign up to set email alerts
|

Prostasin and hepatocyte growth factor B in factor VIIa generation: Serine protease knockdowns in zebrafish

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Prostasin (PRSS8), a serine protease that not only regulates the epithelial sodium channel but is also expressed in endothelial and smooth muscle cells (Zhu et al., 2008), was identified as one of the most upregulated proteins in patients from the Severe group when compared to the UI Control group in both sets of EVs (Figures 3b & 4; Supplementary Figures 4C & 5). Interestingly, prostasin has recently been reported to directly or indirectly convert coagulation Factor VII to its active form (Khandekar et al., 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Prostasin (PRSS8), a serine protease that not only regulates the epithelial sodium channel but is also expressed in endothelial and smooth muscle cells (Zhu et al., 2008), was identified as one of the most upregulated proteins in patients from the Severe group when compared to the UI Control group in both sets of EVs (Figures 3b & 4; Supplementary Figures 4C & 5). Interestingly, prostasin has recently been reported to directly or indirectly convert coagulation Factor VII to its active form (Khandekar et al., 2020).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, this relationship was maintained when metastatic recurrence was excluded as a possible underlying cause of thrombosis. The interaction between HPN and coagulation in this type of cancer could be explained by the ability of HPN to activate proteins such as factor VII, XII and IX of the coagulation cascade (6,7,49), although none of these studies have been done in humans. Another key fact to explain the association between HPN and thrombosis is that, although this protein is described as a transmembrane protease, there are studies that have identified it in the serum of patients with CRC (16).…”
Section: Discussionmentioning
confidence: 99%
“…[32][33][34] Various examples include the two tlr4 genes, 35 four igf genes, 36 two copies of cytokine genes 37 , and two hgf genes. 38,39 The genome duplication may have also given rise to more than one f9 gene in the zebrafish genome whose functions remain uncharacterized. We identified three potential f9 genes in the zebrafish genome, namely, f9a, f9b, and f9l.…”
Section: Discussionmentioning
confidence: 99%
“…This duplication generated paralogous groups of many genes, lending the genes an opportunity to acquire new functions, take over part of the original function, or become inactivated 32‐34 . Various examples include the two tlr4 genes, 35 four igf genes, 36 two copies of cytokine genes 37 , and two hgf genes 38,39 . The genome duplication may have also given rise to more than one f9 gene in the zebrafish genome whose functions remain uncharacterized.…”
Section: Discussionmentioning
confidence: 99%